OPTIMIZATION STUDY OF VOLTAGE MULTIPLIER CIRCUIT STAGES IN RF ENERGY HARVESTER - MAT DAUD, AMIRA SYAFEQAH (2017)
Voltage multiplier is used in radio frequency (RF) energy harvester to increase very low AC input voltage scavenged from RF energy to a higher DC output voltage. A single stage voltage multiplier can be cascaded into multiple stages using Cockroft-Walton voltage multiplier and Dickson charge pump topologies to further increase the output voltage. The simulation is done using Advance Design System (ADS) software for both topologies from two to nine stages of voltage multiplier to measure and verify the input and output voltage and current from the circuits. The input frequency used for this work is 1800 MHz and components are non-polarized capacitor and Schottky diodes, HSMS286B. The values of voltage and current are used to calculate power and efficiency of the circuit. Finally, the optimized stage of voltage multiplier circuit stages is found at three stages, leading to maximum output power generated at load.